Production and Quality of Biodiesel under the Influence of a Rapeseed Fertilization System - Andra Lovasz; Nicu Cornel Sabau; Ioana Borza; Radu Brejea (Energies, 2023)
Compared to fossil fuels, biodiesel is a clean fuel, does not pollute the environment, and can be produced from inexhaustible natural sources. The objectives of our research are to study how increasing doses of complex fertilizers, applied to rapeseed oil culture, affect the production of rapeseeds and oil; the comparative study between the quality parameters of refined rapeseed oil (RRO) and fatty acids (FA); and the analysis of the quality of the biodiesel obtained from them (BRO and BFA). The experimental field is set-up in a Latin rectangle format and is placed on a total area of 400 m2 divided into 16 parcels, randomized for uniformity with four replications and four fertilizer graduations (N0P0K0—Control, N160P160K160, N320P320K320, N480P480K480). To obtain biodiesel form oil (BRO) and fatty acids (BFA), the processes of esterification, transesterification, refining, washing, sedimentation, and drying were applied. A comparison between biodiesel quality parameters from RRO and FAs were made, and we highlighted the differences in quality compared to samples from the experimental field. The use of large amounts of complex fertilizers leads to high yields of rapeseed (13.3–47.0 q ha−1) and oil (629.8–2130.8 L ha−1), which are statistically significant only for high doses (N320P320K320 and N480P480K480). For most of the qualitative parameters studied, the differences in values between BFA and BRO have positive values, which means a higher quality for BRO. Both BRO and BFA generally fall within the quality parameters imposed by European standards (ES). Although the quality of BRO is superior to BFA, it is produced on a smaller scale due to the nutritional importance of refined rapeseed oil. This study is of particular importance in the optimization of rapeseed fertilization, with a view to the efficient conversion of crude oil, a feedstock for chemical fertilizers and an environmentally friendly fuel.